Añora, Spanien: Der Fundplatz ‚La Losilla‘ bei Añora (Córdoba) – eine spätantike Kirche im ländlichen Bereich der Baetica - Schlimbach, Fedor (e-Forschungsberichte des DAI, 2023)
The project addresses the remains of a late antique church at ‚La Losilla‘ near the town of Añora (Córdoba) in Andalusia. Besides these remains, the study of the adjacent cemetery is part of the project. One main goal is the archaeological examination of the context, in which the church was built and used – an aspect rather neglected during the work of the previous decades.